Mitigating the effects of drought through food security monitoring: lessons from Malawi - Babu, Suresh Chandra; Chapasuka, Evance (International Food Policy Research Institute, 1996)
This paper using a case study of Malawi, demonstrates the use of food security and nutrition monitoring system for managing and mitigating the effects of drought. The implementation of Food Security and Nutrition Monitoring during the drought emergency is presented along with a description of the process of information generation and the use of results in emergency interventions. Presenting the lessons learned from the Malawi experience for the benefit of future drought management and disaster prevention efforts in other sub-Saharan African countries, the paper concludes that a decentralized system of data collection, processing, and analysis is more likely to be successful in planning interventions for food security and nutritional improvements during the periods of drought.